Application of Some Starch Hydrogels for the Removal of Mercury(II) Ions from Aqueous Solutions - A. Hashem; F. Ahmad; R. Fahad (Adsorption Science & Technology)
Three types of starch hydrogels were prepared via the graft polymerization of acrylonitrile, AN, onto maize starch using ceric ammonium nitrate, CAN, as the initiator, followed by saponification with sodium hydroxide. The prepared hydrogel samples were characterized by estimating their nitrogen and carboxy group contents, and by the application of FT-IR spectroscopy, thermogravimetric analysis (TGA) and scanning electron microscopy (SEM); in addition, their water retention values, WRVs, were also determined. The feasibility of using these hydrogels to remove Hg(II) ions from aqueous solutions was examined. Factors affecting the adsorption of Hg(II) ions onto the starch hydrogels were studied, including the pH value of the solution, the contact time and the concentrations of the adsorbent and adsorbate. The present study has shown that the prepared hydrogels could be used effectively for the adsorption of Hg(II) ions from aqueous solutions. The adsorption data obtained obeyed the Langmuir and Freundlich isotherms. The adsorption of Hg(II) ions onto the starch hydrogels followed second-order kinetics. An examination was made of the mechanism for the adsorption of Hg(II) ions onto the starch hydrogels.